Targeted in vivo knock-in of human alpha-1-antitrypsin cDNA using adenoviral delivery of CRISPR/Cas9. Issue 2 (April 2018) - Stephens, Calvin; Kashentseva, Elena; Everett, William; Kaliberova, Lyudmila; Curiel, David
Abstract Serum deficiency diseases such as alpha-1-antitrypsin deficiency are characterized by reduced function of serum proteins, caused by deleterious genetic mutations. These diseases are promising targets for genetic interventions. Gene therapies using viral vectors have been used to introduce correct copies of the disease-causing gene in preclinical and clinical studies. However, these studies highlighted that disease-alleviating gene expression is lost over time. Integration into a specific chromosomal site could provide lasting therapeutic expression to overcome this major limitation. Additionally, targeted integration could avoid detrimental mutagenesis associated with integrative vectors, such as tumorigenesis or functional gene perturbation. To test if adenoviral vectors can facilitate long-term gene expression through targeted integration, we somatically incorporated the human alpha-1-antitrypsin gene into theROSA26 "safe harbor" locus in murine livers, using CRISPR/Cas9. We found adenoviral-mediated delivery of CRISPR/Cas9 achieved gene editing outcomes persisting over 200 days. Furthermore, gene knock-in maintained greater levels of the serum protein than provided by episomal expression. Importantly, our "knock-in" approach is generalizable to other serum proteins and supports in vivo cDNA replacement therapy to achieve stable gene expression.